PENGEMBANGAN DESAIN PEMBELAJARAN ICARE BERBANTUAN LEARNING MANAGEMENT SYSTEM UNTUK MENINGKATKAN PROSES PEMBELAJARAN - Aulia, Fikri (Prodi Teknologi Pendidikan, 2017)
Abstract. Learning is a process of education conducted by the teacher to the learner, the learning will be more effective when utilizing media. The development of information and communication technologies have an important role in learning. In addition to media, instructional design is also influential in the learning process. In this study, researchers are interested in researching the development of ICT-assisted with learning design to improve the effectiveness of learning. This research aims to find hipotetik model of instructional design development ICARE assisted learning management system to improve the learning process, in addition to knowing their effectiveness. This type of research is research and development. Defined by the Borg and Gall (2003), that